AC Voltage Induced Electrohydrodynamic Two-Phase Convective Boiling Heat Transfer in Horizontal Annular Channels - ROBINSON, ANTHONY (My University, 2012)
An experimental study of alternating current (AC) induced electrohydrodynamic (EHD) flow and heat transfer augmentation for boiling inside an annular channel containing working fluid refrigerant HFC-134a has been conducted in a single-pass, counter-flow heat exchanger with a rod electrode placed concentric to a grounded tube. Experiments were conducted for an inlet quality of 0%, a heat flux of 10.2 kW/m2, mass fluxes from 100 kg/m2s to 500 kg/m2s and applied voltages from 0 kV to 8 kV DC and 0 kV to 24 kV peak to peak AC. The AC tests were conducted for both low frequency (60 Hz) and high frequency (6.6 kHz) near sinusoidal waveforms. The results show that there is no apparent difference between the DC and the 6.6 kHz AC test cases, whereas the 60 Hz AC tests show significantly different behaviour. The flow boiling heat transfer results indicate that the averaged heat transfer coefficients can be increased by as much as 3-fold for a 24 kV p.p. 60 Hz AC applied voltage. This also incurs a pressure drop penalty of 2.6 fold across the heat exchanger.
PUBLISHED
Keywords: Mechanical Engineering; Electrohydrodynamic; Alternating Current; Convective Boiling